2022
DOI: 10.1039/d2nr00222a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen evolution reaction mechanism on Ti3C2 MXene revealed by in situ/operando Raman spectroelectrochemistry

Abstract: MXenes have shown great promise as electrocatalysts for the hydrogen evolution reaction (HER), but their mechanism is still poorly understood. Currently, the benchmark Ti3C2 MXene suffers from a large overpotential....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…The full data set for this analysis is provided in Figure S2 (supplemental information). This further elucidated the mechanism by showing that electrons were entering the Ti 3 C 2 MXene, leading to an overcharging of the lattice and termination groups [20] . This movement of electrons is what consequently leads to protons being drawn towards the surface.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The full data set for this analysis is provided in Figure S2 (supplemental information). This further elucidated the mechanism by showing that electrons were entering the Ti 3 C 2 MXene, leading to an overcharging of the lattice and termination groups [20] . This movement of electrons is what consequently leads to protons being drawn towards the surface.…”
Section: Resultsmentioning
confidence: 77%
“…This further elucidated the mechanism by showing that electrons were entering the Ti 3 C 2 MXene, leading to an overcharging of the lattice and termination groups. [20] This movement of electrons is what consequently leads to protons being drawn towards the surface. When the oxidative region of the CV was reached, the Raman spectra and electronic environment returned to initial conditions, corresponding to the excess electrons leaving the structure allowing for adsorbed protons to desorb from the structure into the bulk electrolyte.…”
Section: Chemelectrochemmentioning
confidence: 99%
“…We recently showed that the active site for HER on the Mxene catalyst is the À OÀ terminated site on the basal plane. [44] For Ti-based Mxenes, open Ti and O sites are critical for achieving high HER activity. While delaminating multilayer Mxenes into few-to-single layers provide some À OÀ termination sites, the results are difficult to reproduce due to the variability in the delamination procedure.…”
Section: Resultsmentioning
confidence: 99%
“…This difference in overpotential between delaminated and multilayer Ti 3 CN is due to the difference in exposed surface area and termination groups. We recently showed that the active site for HER on the Mxene catalyst is the −O− terminated site on the basal plane [44] . For Ti‐based Mxenes, open Ti and O sites are critical for achieving high HER activity.…”
Section: Resultsmentioning
confidence: 99%
“…This high overpotential value is maybe attributed to the lack of an ideal equilibrium between Ti and O sites in this sample. 44 In the case of the chalcogen decorated Ti 3 C 2 T x MXene composite samples, it already was proven by the XPS characterization (Figures S2 and 2) that the =O content was enhanced slightly after decoration.…”
Section: Hydrogen Evolution Reactionmentioning
confidence: 87%